Building and codification of the emotional equilibrium measure and its relationship with some of the offensive skills of basketball players for the season (2016 - 2017) - Hamidi, A. M.; Motair, K. A.; Mashaav, R. R. (Journal of Human Sport & Exercise, 2019)
The study aimed to: to build the emotional equilibrium measure for basketball youth players to identify the relationship between the emotional equilibrium measure and some of the offensive skills for the basketball youth players in Maysan province. The researchers proposed that there is a statistical relationship between the emotional equilibrium measure and some of the offensive skills for the basketball youth players in Maysan province. The researchers concluded that the effectiveness of the emotional equilibrium measure for the Theoretical and practical aspect of the players, the results of the emotional equilibrium measure for the Chest Pass was moral from the results that the players got, the researchers reached the following recommendation The need to take care of the general psychological preparation of players through the training process with special attention to the development of the skill levels of the basketball players in the Psychological traits especially the emotional equilibrium trait, because the distinguished players with high level emotional equilibrium are more capable to take advantage of their physical ability, skills and following plans which contribute to winning superior then their peers. The exploratory experiment was conducted on 7/7/2016 and up to 72/7/2016 to demonstrate the validity of the scale to a sample of 15 players representing the Ali al-Gharbi Sports Basketball Club in Maysan Governorate. The researchers used the internal consistency coefficient with sincerity of construction and it measures the relationship between the scale total degree and the grades of each paragraph, because the coefficient of differentiation does not determine.